The Influence of The Pedagogical Competence of Homeroom Teachers In Improving Student Learning Outcomes In Arabic Language Subjects Muthola'ah - Adyaksa; Muhamad Fawwaz Rizaka; Ni’matuz Zuhroh (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study examines the effect of teachers' pedagogical competence on student learning outcomes at Pondok Modern Darussalam Gontor Ponorogo, Indonesia. Teachers' pedagogical competence includes lesson planning, management of teaching and learning interactions, and mastery of learning materials, especially in Muthola'ah subjects. This study uses quantitative methods with the hypothesis that teachers' pedagogical competence affects student learning outcomes. The sample consisted of 71 respondents selected using simple random sampling technique. The data collection techniques used were observation, questionnaires, and documentation. The results showed a significant influence between teachers' pedagogical competence on student learning outcomes. Furthermore, the calculated R value (0.722) exceeds the R table value (0.2335), indicating a strong and positive relationship between the two variables. And based on the table of student scores obtained, paying attention to 71 students as a sample, it can be seen that 9 people or 13% are in the low category, 45 people or 63% are in the medium category, and 17 people or 24% are in the high category. Therefore, it can be concluded that the pedagogical competence of teachers has a significant effect on student learning outcomes at Pondok Modern Darussalam Gontor Ponorogo.